2000
DOI: 10.1021/op990202j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of HIV Protease Inhibitor ABT-378 (Lopinavir)

Abstract: A large scale process for the synthesis of HIV protease inhibitor candidate ABT-378 has been developed which utilizes an intermediate common to the synthesis of ritonavir, Abbott's first generation compound. The synthesis relies on the sequential acylation of this intermediate which is carried through as a mixture of diastereomers until the penultimate step. A synthesis of acid 5, derived from L-valine, is also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 15 publications
(12 reference statements)
0
39
0
Order By: Relevance
“…The key intermediates used for SAR studies were synthesized according to a previously reported procedure. 53 …”
Section: Methodsmentioning
confidence: 99%
“…The key intermediates used for SAR studies were synthesized according to a previously reported procedure. 53 …”
Section: Methodsmentioning
confidence: 99%
“…Acid A4 was treated with SOCl 2 in EtOAc, and the resulting acyl chloride was reacted with 1 using the reported procedure. 25 Catalytic debenzylation of intermediate compounds 2-5 using Pd/C provided the free amines 6-9 that were subsequently a Abbreviations: EDCI, 1-ethyl-3-(3′-dimethylaminopropyl)carbodiimide hydrochloride; HOBt, N-hydroxybenzotriazole hydrate; DIPEA, diisopropylethylamine; FRET, fluorescence resonance energy transfer. reacted with the activated carboxylic acids 10 or 11a-f to provide the designed inhibitors 12-16.…”
Section: Chemistrymentioning
confidence: 99%
“…Acyl chloride (8) was prepared by reaction of the corresponding acid (7) with thionyl chloride in the presence of a single drop DMF, 15 and then reacted with the compound (9), lithium di-n-propylcuprate(I), to get the appropriate ketone (10) possessing a npropyl group. 16 a-Phenoxyacetophenone (11) was synthesized from a-bromoacetophenone and phenol in the presence of potassium carbonate.…”
Section: Chemistrymentioning
confidence: 99%